Endogenous market segmentation and the law of one price - Richard Friberg; Kaj Martensen (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
To the surprise of many, price deviations between markets characterized by imperfect competition have often been little affected by lower transport costs. In a Cournot model we show that if firms' decisions to segment markets are endogenous, then lower transport costs are, in many cases, associated with greater price differentials between markets. The intuition is that lower transport costs, by facilitating arbitrage, place a tighter restriction on the maximization problem and a firm is willing to take a greater cost in order to segment. We examine how the resulting equilibria depend on transport costs, product differentiation and costs of segmenting.
Keywords: D43; F15; L13; 330; price discrimination; market integration; law of one price; Marktsegmentierung; Internationaler Preiszusammenhang; Unvollkommener Wettbewerb; Theorie